بلراج مینرا کا علامتی اسلوب - Ali, Ghulam (Zoraiz, 2025)
Balaraj Minra is recognized as one of the pioneers of symbolism in Urdu fiction. This research paper attempts to explore how his symbolic style compels readers to ponder and reflect on the multiple meanings and interpretations a single symbol can hold. It examines how a word can encompass profound depths of meaning and how these can be uncovered. Minra’s stories address a conscious reader who not only delves into their depths but also seeks out the unique meanings and implications of these symbols. He has made human psychology, sexual issues, the complexities facing human existence, and the various torments and trials endured by sensitive individuals the themes of his work. Minra possesses a distinct and unique symbolic system. In his works, a single symbol can carry multiple meanings, and many of the implications hidden within these symbols are yet to be revealed. Over time, as these meanings come to light, they will continue to affirm Minra’s status as a great and distinctive symbolic fiction writer.